2013
DOI: 10.1038/nature11924
|View full text |Cite
|
Sign up to set email alerts
|

Adult somatic stem cells in the human parasite Schistosoma mansoni

Abstract: SummarySchistosomiasis is among the most prevalent human parasitic diseases, affecting more than 200 million people worldwide1. The etiological agents of this disease are trematode flatworms (Schistosoma) that live and lay eggs within the vasculature of the host. These eggs lodge in host tissues, causing inflammatory responses that are the primary cause of morbidity. Because these parasites can live and reproduce within human hosts for decades2, elucidating the mechanisms that promote their longevity is of fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
357
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 199 publications
(374 citation statements)
references
References 38 publications
(57 reference statements)
14
357
0
Order By: Relevance
“…An additional concern is the reliability of morphological/motility changes reflecting parasite viability. It is known that adult schistosomes can recover damaged tegument after sublethal PZQ doses, and recent investigations have identified somatic stem cells in Schistosoma which show potential for tissue regeneration (17,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional concern is the reliability of morphological/motility changes reflecting parasite viability. It is known that adult schistosomes can recover damaged tegument after sublethal PZQ doses, and recent investigations have identified somatic stem cells in Schistosoma which show potential for tissue regeneration (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…To overcome the subjectivity and complexity of microscopy, several novel techniques to determine schistosomulum viability have recently been presented, although microscopy is still the standard reference methodology (12,13,15,16). However, the phenotype and the degree of changes in the worms' morphology and motility heavily depend on the chemical nature of the drug, and in adult worms it has been shown that damaged tissues have the potential to regenerate (17,18). Whether these observations always truly reflect parasite death can only be supposed.…”
mentioning
confidence: 99%
“…Attention has focused on stem cells (also called germinative cells or neoblasts) and the tissues in which they reside because these cells self-replicate as well as differentiate and, hence, endow the evolutionary and developmental plasticity of parasitic flatworms. It is now feasible to isolate gonads enriched in stem cells ( 8), identify somatic proliferating stem cells ( 9), and initiate limited-passage cell cultures from schistosomes ( 14). Also promising are advances in cell cultivation systems for echinococcal tapeworms, where continuous cultures enriched for replicative and differentiating stem cells can be derived from Echinococcus multilocularis ( 10) and "immortal" cell lines can be produced from the closely related species E. granulosus ( 11).…”
Section: Insights | Perspectivesmentioning
confidence: 99%
“…Despite these hurdles, progress in the areas of schistosome (blood fluke) transgenesis ( 7), organ isolation ( 8), and stem cell characterization ( 9), coupled with advances in echinococcal (hydatid tapeworm) primary cell cultures ( 10,11), portends a transformation in the ability to manipulate and study parasitic flatworms. As a prelude to whole organism or cellular transgenesis, techniques have been honed over the past 15 years to perform loss-of-function studies in schistosomes using posttranscriptional gene silencing ( 12).…”
Section: Insights | Perspectivesmentioning
confidence: 99%
“…Little information on the transcription and translation profile of the Vasa gene in S. japonicum exists, although some reports showed that Vasa homologues in Schistosoma mansoni (S. mansoni), named Smvlg1, Smvlg2, and Smvlg3, are transcribed in the posterior ovary (Skinner et al 2012). Furthermore, Vasa, Piwi, Tudor, Tsunagi, and Nanos genes represent potential regulators of proliferating somatic cell (PSC) behavior and could serve as useful markers for these cells in human parasites (Collins et al 2013;Liu et al 2010). …”
Section: Introductionmentioning
confidence: 98%